Integrasi Artificial Intelligence dan Big Data dalam Proses Peradilan Perdata di Indonesia : Tantangan dan Peluang - Maureen Maysa Artiana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The development of information technology, particularly Artificial Intelligence (AI) and Big Data, offers great potential for transforming the judicial system in Indonesia. AI can support legal actors in their duties within the judicial process, while Big Data enables the processing and analysis of large datasets in various formats. In the context of civil litigation, these technologies can be applied in stages such as investigation, prosecution, court decisions, and asset seizure mechanisms. This article examines the challenges and opportunities of integrating AI and Big Data into Indonesia's judicial system. The research uses a normative juridical approach, analyzing Law No. 11 of 2008 on Electronic Information and Transactions, Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Electronic Information and Transactions, as well as relevant legal principles. The findings indicate that AI and Big Data can enhance efficiency, transparency, and accuracy in the judiciary; however, challenges related to technological infrastructure, regulations, and potential issues of privacy or algorithmic bias exist. Therefore, strategic steps are needed, such as developing supportive regulations and providing training for legal professionals to optimize the use of these technologies.